An Advance Study on Dairy Buffalo Development through Investment in Genetic Improvement - Soliman, Ibrahim; Bahgat, Basher (Research Aspects in Agriculture and Veterinary Science Vol. 1, 2021)
Dairy products are an important source of animal protein in Asian countries, especially for nutritionally vulnerable groups and vegetarians. As a result, the approach to increasing domestic milk supply is to increase buffalo milk yield through genetic improvement from the sperm of a selected buffalo sire with a high predicted milk difference. As a case study, data was collected from Artificial Insemination Centers in Egypt to use a dynamic mathematical investment model to estimate the rate of return (IRR) on genetic investment. Aside from the economic variables, the reproductive characteristics and feed efficiency are the most important variables in IRR. The anticipated most likely amount of IRR, 19.71%, was feasible. An increase of 10% in the number of conception services, age at First Calving, and service period would reduce the IRR by 7.51 percent. The IRR would drop by 9% if feed efficiency dropped by 10%. IRR would be reduced by 7% if feed costs, semen prices, and milk prices all fell by 10%. To import buffalo sires' semen of high predicted milk difference at moderate prices till establishment, domestic genetic merit is required.